POTENSI KEUNGGULAN KOMPETITIF SUMBER DAYA KELAUTAN INDONESIA - Azzahra Alifa Ramadhani (LPPM - STIE SAKTI ALAM KERINCI, 2023)
Two-thirds of Indonesia's territory is ocean, so Indonesia has a high marine resource potential. The potential of marine resources, not only fish or seaweed, but includes diverse marine ecosystems, energy and minerals. The potential for Indonesia's marine economic development can become one of the main sources of capital for development, and can provide maximum benefits for the state and people of Indonesia if it is managed innovatively and well. Indonesia has very abundant marine economic potential. Indonesia's comparative advantage in having biodiversity has made Indonesia one of the largest marine product importing countries in the world, one of which is fisheries. However, comparative advantage alone is not enough to face an increasingly competitive world economy so that maritime comparative advantage is gradually transformed into a competitive advantage. This means that policies for managing and developing marine resources must be systemic through technological development and improving the quality of human resources.